INOVASI GURU PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMA PLUS CITRA MADINATUL ILMI BANJARBARU - Rahmawati, Siti; Nadzari, Muhammad Akmal (Program Studi PAI STAI Al Falah Banjarbaru, 2024)
Abstract: The Independent Curriculum is a new approach in the national education system that requires innovation in the learning process. An independent curriculum is interpreted as a learning design that provides students with the opportunity to study calmly, relaxed, fun, stress-free and pressure-free, to show their natural talents. Merdeka Belajar focuses on freedom and creative thinking. One of the programs outlined by the Ministry of Education and Culture in launching independent learning was the start of a driving school program. This school program is designed to support each school in creating a generation of lifelong learners who have the personality of Pancasila students. For the success of all this, the role of a teacher is needed. In this research, the problem formulation is how the innovation of Islamic Religious Education and Character Education teachers in implementing the Merdeka curriculum at SMA Plus Citra Madinatul Ilmi Banjarbaru and what factors influence the innovation of Islamic Religious Education and Character Education teachers in implementing the Merdeka curriculum in high school. Plus Citra Madinatul Ilmi Banjarbaru. This research aims to investigate the innovations carried out by Islamic religious education teachers in implementing the Merdeka Curriculum. This research uses a qualitative approach with a case study method. Data was collected through classroom observations, in-depth interviews with teachers, and analysis of documents related to curriculum and learning innovation. The innovation of Islamic religious education teachers in implementing the Independent Curriculum has had a positive impact on the learning process. This innovation makes a significant contribution to improving the quality of Islamic religious education at the school level. However, the challenges faced must also be handled wisely so that the full potential of the Independent Curriculum can be realized. It is hoped that the results of this research can contribute to the development of more innovative and effective Islamic religious education in the future.Keywords: Independent Curriculum, Innovation. Abstrak: Kurikulum Merdeka merupakan pendekatan baru dalam sistem pendidikan nasional yang menuntut adanya inovasi dalam proses pembelajaran. Kurikulum merdeka dimaknai sebagai desain pembelajaran yang memberikan kesempatan kepada siswa untuk belajar dengan tenang, santai, menyenangkan, bebas stres dan bebas tekanan, untuk menunjukkan bakat alaminya. Merdeka belajar berfokus pada kebebasan dan pemikiran kreatif. Salah satu program yang dipaparkan oleh Kemendikbud dalam peluncuran merdeka belajar ialah dimulainya program sekolah penggerak. Program sekolah ini dirancang untuk mendukung setiap sekolah dalam menciptakan generasi pembelajar sepanjang hayat yang berkepribadian sebagai siswa pelajar Pancasila. Untuk keberhasilan semua itu dibutuhkan peran seorang guru. Dalam penelitian ini yang menjadi rumusan masalah adalah Bagaimana inovasi guru Pendidikan Agama Islam dan Budi Pekerti dalam implementasi kurikulum Merdeka di SMA Plus Citra Madinatul Ilmi Banjarbaru dan Faktor-faktor apa saja yang mempengaruhi inovasi guru Pendidikan Agama Islam dan Budi Pekerti dalam implementasi kurikulum Merdeka di SMA Plus Citra Madinatul Ilmi Banjarbaru. Penelitian ini bertujuan untuk menginvestigasi inovasi yang dilakukan oleh guru pendidikan agama Islam dalam implementasi Kurikulum Merdeka. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi kelas, wawancara mendalam dengan guru, dan analisis dokumen terkait kurikulum dan inovasi pembelajaran. Inovasi guru pendidikan agama Islam dalam implementasi Kurikulum Merdeka telah membawa dampak positif dalam proses pembelajaran. Inovasi tersebut memberikan kontribusi yang berarti dalam meningkatkan kualitas pendidikan agama Islam di tingkat sekolah. Namun, tantangan-tantangan yang dihadapi juga harus ditangani dengan bijaksana agar potensi penuh dari Kurikulum Merdeka dapat terwujud. Diharapkan hasil penelitian ini dapat memberikan kontribusi bagi pengembangan pendidikan agama Islam yang lebih inovatif dan efektif di masa depan. Kata Kunci: Inovasi, Kurikulum Merdeka.